CHEMICAL COMPOSITION OF THE VOLYN' GRANITES AND PEGMATITES - Gramenitskiy Y.N.; Pham T.X. (My University, 1987)
Compositional differences between pegmatite and its parent rocks in an earlier article were shown to be basic to solving the problem of the mode of separation of pegmatite melt. In that article, though, such differences were based on single pairs of analyses for rock complexes of different regions and ages and were relatively small. Therefore, the question of whether they are reliable must now be considered. We have used statistical tests to settle this question for the Korosten' batholith. The pegmatite bodies in the Korosten' batholith are clustered within a belt fringing the granite contact with rocks of the Volodarsk Volynskiy pluton. The granites of this pegmatite belt are petrographically different from those forming the larger part of the batholith. Preliminary statistical evaluation of analyses and plotting histograms of oxide concentrations revealed the inhomogeneity of the overall sample of granite analyses; the histograms for most oxides proved bimodal.